Undergraduate Students' Knowledge, Attitudes and Willingness to Receive COVID-19 Vaccines: A Survey of Convenience Sample in Namibia - Nestor Tomas RN, RM, RCN, RT, MPH; Takaedza Munangatire RN, BN Sc (Hons); Stefanus Nampila BN Sc (Clinical) (SAGE Publishing, 2023)
Introduction The global consequences of the COVID-19 pandemic cannot be overstated. Vaccinations are one of the leading strategies to protect against the virus, and it is likely that students' understanding and desire to be vaccinated can be major factors in helping contain the pandemic. Nonetheless, no studies looked into the vaccine attitude, knowledge and willingness in Namibia. Objectives To assess and describe the association between knowledge, attitudes, and willingness of undergraduate students to receive COVID-19 vaccines in the school of education, nursing and economics and management science at the university campus in Namibia. Methods The study employed a cross-sectional descriptive study from 203 undergraduate university students using a convenience sampling. Data analysis was done using SPSSv28 and descriptive statistics were used to depict trends in data while a Pearson's correlation determined the relationship between the study variables. Results The data showed that 54.2% (1.54  ±  0.49) of the participants had adequate knowledge concerning the vaccine, while 57.1% and 58.6% had a negative outlook and were unwilling to get vaccinated. A moderate positive correlation was observed between attitudes and willingness to take COVID-19 vaccines ( r   =  .546, P   =<.001), while a negative relation existed between knowledge and attitudes ( r   =  −.017, P   =>.001). Conclusions This study has provided valuable insight into the knowledge, attitudes, and willingness of undergraduate students to receive COVID-19 vaccines. Despite more than half of the participants having appropriate knowledge, they had an unfavourable outlook toward COVID-19 vaccination. It is recommended that further studies focus on how factors such as incentives, religion and cultural values affect their desires to be vaccinated.